2021
DOI: 10.1155/2021/6650958
|View full text |Cite
|
Sign up to set email alerts
|

Association between Novel Marker (Platelet-Lymphocyte Ratio, Neutrophil-Lymphocyte Ratio, and Delta Neutrophil Index) and Outcomes in Sudden Cardiac Arrest Patients

Abstract: Purpose. It is important that clinicians accurately predict the outcome of patients with sudden cardiac arrest (SCA). The complete blood count (CBC) is an easy and inexpensive test that provides information on blood content. Platelet-lymphocyte ratio (PLR), neutrophil-lymphocyte ratio (NLR), and delta neutrophil index (DNI) are relatively novel biomarkers that have been used in the prognosis of various diseases. We aimed to determine the usefulness of PLR, NLR, and DNI in predicting the outcomes of SCA. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…After applying all inclusion and exclusion criteria, 118 studies were included in the scoping review, as shown in Figure 1 . 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After applying all inclusion and exclusion criteria, 118 studies were included in the scoping review, as shown in Figure 1 . 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ,…”
Section: Resultsmentioning
confidence: 99%
“…The search strategy identified a total of 11,834 records, of which 6914 were non‐duplicates. After applying all inclusion and exclusion criteria, 118 studies were included in the scoping review, as shown in Figure 1 11–128 …”
Section: Resultsmentioning
confidence: 99%
“…These may be molecular signatures referencing a neutrophil-to-lymphocyte ratio imbalance (NLR). NLR is a well-documented feature of many severe inflammatory conditions including sepsis ( 76 ), heart failure and other conditions ( 77 ), trauma ( 78 , 79 ) and cardiac arrest ( 80 83 ) and is indicative of a poor outcome. Elevated neutrophil and reduced lymphocyte counts have been associated with poor outcomes in emergency medicine in general ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of SCAs can help physicians during triage, treatment, and overall related management [7]. Biomarkers represent an area of growing interest in this field as they may provide clinicians with early information on the severity of organ dysfunction and enable them to make decisions on clinical strategies and evaluate potential outcomes [8,9]. Similar to worldwide findings, noncardiac causes of SCA are more common in Korea [10].…”
Section: Introductionmentioning
confidence: 95%